2015
DOI: 10.1021/acscatal.5b01043
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Homogeneous Palladium-Catalyzed N-Alkylation of Amines with Alcohols

Abstract: DFT methods and the energetic span model have been used to study the mechanism of the N-alkylation of amines with alcohols catalyzed by the PdCl 2 /dppe/LiOH system (dppe = 1,2-Bis(diphenylphosphino)ethane). The energetic results indicate the most favorable pathway is the inner-sphere hydrogen transfer pathway, which consists of initiation of the threecoordinated active alkoxide complex [Pd(PhCH 2 O)(dppe)] + (Int4i) and the catalytic cycle CC1. Initiation of Int4i includes two sequential steps: (i) generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 94 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…[5] In this context, several homo-and heterogeneous catalytic systems based on Ru, Rh, Ir, Pd, Pt, Mn, Fe, Cr, Co, Ni, have been developed to prepare the N-alkylated amines in an efficient manner. [6][7][8] Although the reported catalyst systems are quite effective, most of the homogeneous based catalytic systems were designed using a combination of a metal salt and precious organic ligand, which sometimes may require multistep synthesis. [6][7][8] On the other hand, heterogeneous based metal catalysts also suffer from high catalyst loading, selectivity, and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In this context, several homo-and heterogeneous catalytic systems based on Ru, Rh, Ir, Pd, Pt, Mn, Fe, Cr, Co, Ni, have been developed to prepare the N-alkylated amines in an efficient manner. [6][7][8] Although the reported catalyst systems are quite effective, most of the homogeneous based catalytic systems were designed using a combination of a metal salt and precious organic ligand, which sometimes may require multistep synthesis. [6][7][8] On the other hand, heterogeneous based metal catalysts also suffer from high catalyst loading, selectivity, and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Although the reported catalyst systems are quite effective, most of the homogeneous based catalytic systems were designed using a combination of a metal salt and precious organic ligand, which sometimes may require multistep synthesis. [6][7][8] On the other hand, heterogeneous based metal catalysts also suffer from high catalyst loading, selectivity, and harsh reaction conditions. [9][10] Thus, the development of lowcost metal catalysts [11] or efficient catalytic systems with high turnover numbers under mild reaction conditions [12] toward the synthesis of N-alkylation reaction is highly desirable and always remains in demand.…”
Section: Introductionmentioning
confidence: 99%
“…On one side, this condensation has been considered rapid and easily accomplished without the intervention of the catalyst by some authors. [ 53–55 ] Other authors have reported that this process is more favored by water [ 56 ] or alcohols [ 57 ] than by some metallic species. In contrast, other theoretical [ 21,58,59 ] and experimental [ 21 ] studies indicate that the condensation step takes place in the coordination sphere of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The most straightforward synthesis of chiral alkylamines is arguably direct N‐alkylation of amines using cheap, readily available alcohols by the so‐called “borrowing hydrogen reaction” or hydrogen autotransfer reaction (Scheme a) . A typical process involves dehydrogenation of an alcohol to form a ketone by a metal catalyst, in situ condensation to a ketimine, and subsequent addition of the metal hydride catalyst . No prior chemical activation of alcohols is needed and ideally water is the only byproduct.…”
Section: Figurementioning
confidence: 99%